Open circuit fault detection and diagnosis in matrix converters - Brunson, C.; Empringham, Lee; De Lillo, Liliana; Wheeler, Patrick; Clare, Jon C. (Institute of Electrical and Electronics Engineers, 2014)
With the increased use of power electronics in aerospace, automotive, industrial, and energy generation sectors, the demand for highly reliable and power dense solutions has increased. Matrix converters become attractive when taking into account demands for high reliability and high power density. With their lack of large bulky DC-link capacitors, high power densities are possible with the capability to operate with high ambient temperatures. When a power converter needs high reliability, under tight weight and volume constraints, it is often not possible to have an entirely redundant system. Taking into account these constraints it is desirable that the power converter continue to operate even under faulty conditions, albeit with diminished performance in some regard. This paper presents an open circuit switch fault detection and diagnosis system for matrix converters, which has been experimentally validated. The presented system requires no load models, averaging windows or additional sensors, this makes the proposed method fast and low cost.